2010
DOI: 10.1210/jc.2009-2103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proto-Oncogene Mutation Detection in Cytological Specimens from Thyroid Nodules Improves the Diagnostic Accuracy of Cytology

Abstract: Our findings demonstrate that molecular analysis of cytological specimens is feasible and that its results in combination with cytology improves the diagnostic performance of traditional cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
234
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(257 citation statements)
references
References 17 publications
21
234
0
2
Order By: Relevance
“…10,12 Moreover, we detected 10/48 mutated samples (21%) with a higher incidence of RAS variants in comparison with previous reports in Thy 3 patients. 10,16 In addition to establishing the evident advantages of HRM prescreening in terms of time and economic improvement, this pilot study confirmed the accuracy of the proposed method. Complete concordance was found between the standard protocol, based on sequencing of all samples, and the HRM-based screening.…”
Section: Discussionsupporting
confidence: 56%
“…10,12 Moreover, we detected 10/48 mutated samples (21%) with a higher incidence of RAS variants in comparison with previous reports in Thy 3 patients. 10,16 In addition to establishing the evident advantages of HRM prescreening in terms of time and economic improvement, this pilot study confirmed the accuracy of the proposed method. Complete concordance was found between the standard protocol, based on sequencing of all samples, and the HRM-based screening.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies have demonstrated the feasibility of mutations detection in clinical FNAB samples, extensively BRAF and RAS mutations, and the improvement of accuracy of FNAB especially in indeterminate cytology. Detection of other molecular markers such as as RET/PTC and PAX8/PPARg mutations does not contribute substantially to cancer diagnosis and in addition, they are technically more difficult to study (18).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies demonstrated that the sensitivity of molecular assays has improved by combined detection of BRAF and RET/PTC. An increased sensitivity from about 42.3-69% to 56.4-78% has been reported [196][197][198].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 90%
“…TRK rearrangements may also be added to this panel. Presence of BRAF, RAS, RET/PTC, PAX8-PPAR␥ and TRK in FNAB samples correlated with malignancy in 97% of cases [196,197,212]. Therefore, detection of any mutation of this panel is a strong predictor for thyroid cancer.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 98%